Hypertension Is Associated With Preamyloid Oligomers in Human Atrium: A Missing Link in Atrial Pathophysiology?. Issue 6 (2nd December 2014) - Sidorova, Tatiana N.; Mace, Lisa C.; Wells, K. Sam; Yermalitskaya, Liudmila V.; Su, Pei‐Fang; Shyr, Yu; Atkinson, James B.; Fogo, Agnes B.; Prinsen, Joseph K.; Byrne, John G.; Petracek, Michael R.; Greelish, James P.; et al.
Abstract : Background: Increasing evidence indicates that proteotoxicity plays a pathophysiologic role in experimental and human cardiomyopathy. In organ‐specific amyloidoses, soluble protein oligomers are the primary cytotoxic species in the process of protein aggregation. While isolated atrial amyloidosis can develop with aging, the presence of preamyloid oligomers (PAOs) in atrial tissue has not been previously investigated. Methods and Results: Atrial samples were collected during elective cardiac surgery in patients without a history of atrial arrhythmias, congestive heart failure, cardiomyopathy, or amyloidosis. Immunohistochemistry was performed for PAOs using a conformation‐specific antibody, as well as for candidate proteins identified previously in isolated atrial amyloidosis. Using a myocardium‐specific marker, the fraction of myocardium colocalizing with PAOs (PAO burden) was quantified (green/red ratio). Atrial samples were obtained from 92 patients, with a mean age of 61.7±13.8 years. Most patients (62%) were male, 23% had diabetes, 72% had hypertension, and 42% had coronary artery disease. A majority (n=62) underwent aortic valve replacement, with fewer undergoing coronary artery bypass grafting (n=34) or mitral valve replacement/repair (n=24). Immunostaining detected intracellular PAOs in a majority of atrial samples, with a heterogeneous distribution throughout the myocardium. Mean green/red ratio value for the samples was 0.11±0.1 (range 0.03 to 0.77), with a value ≥0.05 in 74 patients. Atrial natriuretic peptide colocalized with PAOs in myocardium, whereas transthyretin was located in the interstitium. Adjusting for multiple covariates, PAO burden was independently associated with the presence of hypertension. Conclusion: PAOs are frequently detected in human atrium, where their presence is associated with clinical hypertension.